1986
DOI: 10.1111/j.1746-1561.1986.tb05692.x
|View full text |Cite
|
Sign up to set email alerts
|

Children of Alcoholics: Breaking the Cycle

Abstract: “Please send me some pamphlets. I am twelve‐and‐a‐half years old. Please hurry. I can't stand it anymore. My father's drinking.”

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Identification of adult COAs was assessed by the Children of Alcoholics Screening Test (Jones, 1983). Of the participants, more than 70% were non-COAs, which is consistent with the national population estimates of adult COAs (Woodside, 1986).…”
Section: Methods Participantssupporting
confidence: 84%
“…Identification of adult COAs was assessed by the Children of Alcoholics Screening Test (Jones, 1983). Of the participants, more than 70% were non-COAs, which is consistent with the national population estimates of adult COAs (Woodside, 1986).…”
Section: Methods Participantssupporting
confidence: 84%
“…Because of the family secret, they dare not bring others home for fear of embarrassment and the ensuing shame and stigma of public exposure. 8 Frequently, children of alcoholics may be ill more often than other youngsters and visit the school nurse complaining of abdominal pain, headaches, tics, and nausea, all of which have no physical cause. 8 The exact cause of the illness may be difficult to pinpoint due to vagueness of symptoms.…”
Section: Family and School Interactionmentioning
confidence: 99%
“…It is known that ACOAs are more prone to chemical dependence than the general population (Goodwin, 1971;Sullivan, 1987;Woodside, 1986). Indeed, in one study of nurse alcoholics it was found that 59 percent of those surveyed were ACOAs (Stammer, 1988).…”
Section: No 4 1987/88mentioning
confidence: 99%